Heritage and landscape change: Recording, archiving and engaging with photogrammetry on the Jurassic Coast World Heritage Site. Issue 3 (June 2019) - Ferraby, Rose; Powlesland, Dominic
Abstract: The Jurassic Coast World Heritage Site is a landscape defined by change and process. As such, the approach to its heritage must be similarly flexible and active. A balance must be found between celebrating these processes of change, whilst also conserving those invaluable discoveries and features that so define this coast, as well as encouraging ongoing research and public engagement. This delicate task can be aided firstly by thinking about this geologically defined World Heritage Site as a landscape. In this way it is possible to develop rich and nuanced narratives between the human and geological. Secondly, by embracing new technologies and methodologies to record, archive and communicate features and finds, as well as the process of change itself. Here, we explore these ideas through two unique sites of geological and palaeontological interest discovered in the process of quarrying. To balance keeping the sites open to the public with the risk of natural and human damage to the sites, Structure-from-Motion photogrammetry was used to create accurate, high-resolution, georeferenced 3D models. The process and potentials of the technique are discussed, alongside a discussion of the broader ideas of heritage and approaches already at play on this coastline.